Drug rash with eosinophilia and systemic symptoms syndrome induced by carbamazepine: Case report (2017)
Drug rash with eosinophilia and systemic symptoms (DRESS) syndrome is a hypersensitivity reaction associated with a variety of drugs, mainly anticonvulsants, which is characterized by systemic symptoms and erythematous lesions, common to other toxicodermas. It is an uncommon clinical entity that requires a high suspicion by clinical staff given its varied initial presentation, and the fact that symptoms can overlap with those of other adverse cutaneous reactions to drugs. Without early diagnosis and appropriate treatment, mortality increases.We report the case of a 22-year-old patient with impaired neurodevelopment who received treatment with carbamazepine. Two months later he presented with general symptoms and skin erythematous lesions that began on his trunk. The patient received outpatient care with antihistamines and antipyretics without an appropriate response. His case progressed with increased skin lesions and systemic symptoms that met the diagnostic criteria for DRESS syndrome. He was hospitalized and received medical treatment according to recommended guidelines. The patient's condition improved as his symptoms and associated complications resolved. He was discharged with gradual clearing of the steroid therapy.